Pedagogical and Psychological Factors of Speech Disorders in Preschool Children (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article analyzes the psychological and pedagogical factors of speech disorders in preschool children. Phonational and semantic-structural speech disorders (dyslalia, rhinolalia, dysarthria, alalia, and aphasia) are discussed with examples. Psychological, family, and pedagogical factors influencing speech development are identified, and recommendations for correction and development are provided. The article emphasizes the importance of pedagogical and speech therapy approaches in strengthening children’s speech and social skills.